MAINSTREAMING THE KNOWLEDGE OF ISLAMIC EDUCATION WITH PROGRESS AND OF ISLAM NUSANTARA EDUCATION - Suyadi Suyadi (Akademika : Jurnal Pemikiran Islam, 2019)
The knowledge of Indonesian Islamic education is still strongly influenced by Middle Eastern Islamic education, which is currently experiencing political turmoil and bloodshed due to the transnationalism and global Salafism movement. If this condition continues, Indonesian Islamic education will suffer the same fate. In such a situation, Islamic education with progress and Islam Nusantara education must appear prominent, becoming the mainstream (mainstreaming) as a stronghold of the NKRI. Although some studies deliberately make the difference between them, they have the potential for conflict, but the principle of caring for diversity must be put forward. Library research with this qualitative approach formulates the scientific mainstreaming of Islamic education with progress and Islam Nusantara education amidst the flow of transnational Islamic education. The findings of this study indicate that the scientific advancement of Islamic education with progress is Al-Islam and Kemuhammadiyahan (AIK) while that of Islam Nusantara education is Aswaja. AIK develops knowledge that supports the local wisdom and diversity, while Aswaja maintains local wisdom and national character through science. Both represent the science of moderate Islamic education that is more enlightening than Middle Eastern Islam; thereby, it has the potential to promote Indonesia as a barometer of Islamic world education. Keywords: Islamic education, Kemuhamamdiyahan, and Aswaja